2018
DOI: 10.1109/tit.2017.2750674
|View full text |Cite
|
Sign up to set email alerts
|

Diophantine Equations With Binomial Coefficients and Perturbations of Symmetric Boolean Functions

Abstract: Abstract. This work presents a study of perturbations of symmetric Boolean functions. In particular, it establishes a connection between exponential sums of these perturbations and Diophantine equations of the form To be specific, it is proved that, excluding the trivial cases, balanced perturbations of fixed degree do not exist when the number of variables grows. Some sporadic balanced perturbations are presented. Finally, a beautiful but unexpected identity between perturbations of two very different symmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In other words, A natural problem to explore is to see how solutions to (3.14) given by exponential sums of linear combinations of elementary symmetric polynomials look like as n grows. Perhaps something similar to the study presented in [5] holds true in this case. This is part of future research.…”
Section: A Formula For Exponential Sums In Terms Of Multinomial Sumssupporting
confidence: 80%
“…In other words, A natural problem to explore is to see how solutions to (3.14) given by exponential sums of linear combinations of elementary symmetric polynomials look like as n grows. Perhaps something similar to the study presented in [5] holds true in this case. This is part of future research.…”
Section: A Formula For Exponential Sums In Terms Of Multinomial Sumssupporting
confidence: 80%
“…Fine proposed as problems the veracity of the other properties for general p. O. Aberth [1] disproved (2) and (5) by showing that p (5) 6 (0) = 1/5 and p (5) 6 (2) = 26/125. He also showed that p (5) 30 (0) = 15749/78125 > 1/5 = p (5) 6 (0) and therefore (4) is also false. In [26], J. D. Smith generalized Aberth's example and showed that if p > 3 is prime, then As mentioned at the beginning of Section 2, one of the reasons the asymptotic behavior of exponential sums of symmetric polynomials was calculated over the binary field was to provide an asymptotic proof of Conjecture 2.1 (see [6]).…”
Section: (Q)mentioning
confidence: 99%
“…Many problems in number theory and combinatorics, as well as in their applications, can be formulated in terms of exponential sums. In cryptography, for example, exponential sums can be used to detect when a particular function is balanced (a property very useful in cryptographic applications) [5,6,7,8,9,12,13]. Some classical examples of exponential sums include the number-theoretical Gauss sums, Kloosterman sums, and Weyl sums.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of non-constant symmetric Boolean functions, which can be represented by a polynomial of only one variable, defined on {0, 1, ..., n}, with the degree less than the expected one, namely n (using Lagrange interpolation), became of special interest for obtaining various cryptographic properties (see Gopalakrishnan et al [8], Cusick and Li [3], Mitchell [9], Sarkar and Maitra [11] and more recent works such as Castro, Gonzalez and Medina [1]). A symmetric Boolean function with this special property is now referred to as balanced.…”
Section: Introductionmentioning
confidence: 99%